Motivation, Perceptions, and Preferences of Tourists Visiting National Parks on the Java and Sulawesi Islands - Bukit, Windi Liani; Kusrini, Mirza D.; Rachmawati, Eva; Dewi, Tungga; Adinda, Esther; Hapsari Ayuningtyas, Aniis (Department of Forest Resources Conservation and Ecotourism - IPB University, 2025)
Understanding tourist motivation, perception, and preferences is critical for designing effective tourism strategies in national parks. This study examines the relationship between ecological factors and the motivations, perceptions, and preferences of domestic tourists visiting national parks in Java and Sulawesi, Indonesia. Data were collected from 358 respondents via an online survey over four months and analyzed using chi-square and General Linear Model tests to assess socio-demographic differences. The main motivation for visiting national parks in Java was